Experimental and Theoretical Studies of Volatile Corrosion Inhibitors Adsorption on Zinc Electrode - Teixeira, Deiver Alessandro [UNESP]; Valente Jr., Marco A. G. [UNESP]; Benedetti, Assis Vicente [UNESP]; Feliciano, Gustavo Troiano [UNESP]; Silva, Sebastião C. Da; Fugivara, Cecilio Sadao [UNESP] (Sociedade Brasileira de Química, 2015)
This study evaluates the interaction of volatile corrosion inhibitors (VCIs) of the amino group with the zinc or zinc oxide surface by means of computational calculations using density functional theory (DFT) and comparing with experimental methods such as electrochemical impedance spectroscopy (EIS) and wet chamber tests. The application of these methods allowed indicating the most promising VCI and understanding its mechanism of action. Thus, after the vaporization of VCI molecules, they condense on the surface and form a protective film or a film with oxidizing characteristic, thereby preventing the corrosive action of the chemical species present in the environment.
Keywords: volatile corrosion inhibitors; density functional theory; electrochemical impedance spectroscopy; wet test chamber